#TITLE_ALTERNATIVE# - ABDUL ROHMAN (NIM 10704048), MAMAN
Active subtance in mosquito repellent lotion must be determined to assure its quality by validated analytical method. This research purposed to develop a gas chromatography for analyzing diethyl toluamide; active substance in mosquito repellent lotion. The lotion was extracted with mixture of ethanolchloroform (1:3) then was diluted with the same solvent. This solution was analyzed by gas chromatography on an OV1 cappilary column as stationary phase, nitrogen as mobile phase and flame ionization detector. The method has been validated by testing its accuracy, precision, limit of detection, limit of quantitation, and linierity. Its recovery from spiked sample ranged from 97,6 to 101,18%, the precision with the coefficient of variation of 1,12 %, linierity with the coefficient of correlation of 0,9996, and the coefficient variation of regression function of 1,811%, limit of detection was 0,031 mg/ml and limit of quantitation of 0,1 mg/ml. The validated gas chromatography method had been used for analyzing diethyl toluamide in commercial mosquito repellent lotion succesfully